2020
DOI: 10.2147/ott.s245813
|View full text |Cite
|
Sign up to set email alerts
|

<p>HSP90 Inhibitor Ganetespib (STA-9090) Inhibits Tumor Growth in c-Myc-Dependent Esophageal Squamous Cell Carcinoma</p>

Abstract: Purpose: Currently, the paucity of classical effective pharmacological drugs to treat esophageal squamous cell carcinoma (ESCC) is a major problem. The c-Myc (MYC) protein is a promising target as it is overexpressed in ESCC. MYC is a sensitive client protein of the heat shock protein 90 (HSP90) and, therefore, targeting the HSP90-MYC axis by inhibition of HSP90 is a potential therapeutic strategy for ESCC. Here, we evaluated the clinical application value of the HSP90 inhibitor (Ganetespib, STA-9090) as an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…Guan et al . ( 45 ) found that ganetespib treatment caused an increase in cell cycle–dependent kinase inhibitors p15 and p21 in c-Myc–dependent esophageal squamous cell carcinoma. Ganetespib significantly represses CDK1 expression and caused G2 block and mitotic arrest in thyroid cancer cells ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Guan et al . ( 45 ) found that ganetespib treatment caused an increase in cell cycle–dependent kinase inhibitors p15 and p21 in c-Myc–dependent esophageal squamous cell carcinoma. Ganetespib significantly represses CDK1 expression and caused G2 block and mitotic arrest in thyroid cancer cells ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…E2F1 has been attributed to numerous cancer hallmarks in prostate cancer, including cell cycle, proliferation and apoptosis [ 45 ], and its expression is so closely aligned with disease stage that it has been proposed as a potential biomarker [ 46 , 47 ]. Notably, AR, MYC and E2F1/2 are all established Hsp90 client proteins, and targeting Hsp90 inhibits expression of AR in prostate cancer (reviewed in [ 41 ]), and MYC [ 48 , 49 , 50 , 51 ] and E2F1 [ 52 , 53 ] in other cancers. Our ability to identify known pathways associated with Hsp90 and prostate cancer through omics analysis of PDE tissues highlights the capacity for omics identification of novel targets and biomarkers in the face of prostate tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…cisplatin) and radiation play inhibitory roles in EC cell survival. For instance, the inhibitor of HSP90 Ganetespib (STA-9090) could inhibit cell proliferation and induce apoptosis in ESCC cells and PDX models [ 148 ]. Interestingly, the effect of HSP90 inhibition seemed to be dependent on MYC expression.…”
Section: Application Of Pdx Models In Evaluating Therapeutic Targets For Chemotherapymentioning
confidence: 99%
“…Interestingly, the effect of HSP90 inhibition seemed to be dependent on MYC expression. ESCC cells and xenografted primary tumors overexpressing MYC were more sensitive to STA-9090 [ 148 ].…”
Section: Application Of Pdx Models In Evaluating Therapeutic Targets For Chemotherapymentioning
confidence: 99%